Health websites visual structure: the necessity of developing a comprehensive design guideline - Valizadeh-Haghi, Saeideh; Moghaddasi, Hamid; Rabiei, Reza; Asadi, Farkhondeh (Archives of Advances in Biosciences, 2017)
Using health-related websites and their information increasingly develops and some concerns on its quality arise as well. Different factors affect the quality of health websites which visual structure is one of the most important factors. The aim of the current study is to explain the role of health websites` visual structure in users’ views on their quality and reliability as well as its role in obtaining health information by users. Furthermore, the need for a comprehensive guideline for designing such websites is discussed. The review showed that health website’s appearance has an important role in users view on its credibility. Furthermore, it was revealed that there is no comprehensive national or international guideline to health websites design. Considering the importance of visual structure of health websites, there is an emergent need to develop a national guideline to obviate the problems of non-consistent, poor or personalized design of health websites.